Aktivitas Sedatif Ekstrak Etanol Batang Tali Kuning (Anamirta cocculus (L.) Wight & Arn.) Terhadap Mencit (Mus musculus) Jantan - Wiwit Ayu Fitrianti; A.M. Muslihin; Ratih Arum Astuti (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Mental health is a state of well-being that includes where individuals recognize their personal potential, enabling them to manage life's pressures and be able to work productively. Treatment of mental health disorders usually involves the use of sedative drugs such as benzodiazepines, barbiturates, and several other drugs. This study aims to evaluate the sedative activity of the ethanol extract of tali kuning (A. cocculus (L.) Wight & Arn.) stem in male mice as an alternative therapy requiring sedative effects. The study was conducted using a quantitative experimental approach with a pretest–posttest control group design and the rotarod method. The experimental animals were divided into five groups: positive control, negative control, and three extract dose groups treated with the ethanol extract of tali kuning stem at 19.25 mg/kgBW, 38.5 mg/kgBW, and 77 mg/kgBW. The results indicated that the ethanol extract of tali kuning stem at all three doses produced sedative activity, as validated by a paired sample t‑test that revealed significant differences condition between pre‑ and post‑treatment measurements. The ethanol extract of tali kuning stem at doses of 19.25 mg/kgBW, 38.5 mg/kgBW, and 77 mg/kgBW demonstrated sedative activity, although statistical comparison with the positive control showed variable results depending on dose and observation time.